2014
DOI: 10.1007/s10701-014-9839-4
|View full text |Cite
|
Sign up to set email alerts
|

Ontological Models, Preparation Contextuality and Nonlocality

Abstract: The ontological model framework for an operational theory has generated much interest in recent years. The debate concerning reality of quantum states has been made more precise in this framework. With the introduction of generalized notion of contextuality in this framework, it has been shown that completely mixed state of a qubit is preparation contextual. Interestingly, this new idea of preparation contextuality has been used to demonstrate nonlocality of some ψ-epistemic models without any use of Bell's in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 31 publications
1
28
0
Order By: Relevance
“…Furthermore, we show that restricted preparation contextuality of quantum theory leads to its limited nonlocal behavior as depicted in the Cirel'son bound. Therefore, our result brings the qualitative connection between preparation contextuality and nonlocality explored in [12][13][14] to a quantitative footing.…”
Section: Arxiv:150605174v2 [Quant-ph] 12 Sep 2015mentioning
confidence: 57%
See 3 more Smart Citations
“…Furthermore, we show that restricted preparation contextuality of quantum theory leads to its limited nonlocal behavior as depicted in the Cirel'son bound. Therefore, our result brings the qualitative connection between preparation contextuality and nonlocality explored in [12][13][14] to a quantitative footing.…”
Section: Arxiv:150605174v2 [Quant-ph] 12 Sep 2015mentioning
confidence: 57%
“…It was then shown that mixed preparations (density matrices) in quantum theory exhibit preparation contextuality [9,12]. Interestingly, invoking another non-classical concept called steering [10,11] along with this new idea of preparation contextuality one can establish nonlocality of QM without using any Bell type inequalities; it has been shown that nonlocality of some hidden variable models, underlying QM, directly follows from the steerability of bipartite pure entangled states and the preparation contextuality of mixed states [12][13][14].The traditional definition of contexuality address to only the contexts of projective measurements, which has been studied in much depth [15,16]. However, generalized notion of contextuality developed by Spekkens define three different types of contexts: measurement (generalized), preparation, and transformation contexts [9].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…It is also known that preparation noncontextual models underlying quantum theory must be maximally epistemic, and these in turn must be Kochen-Specker noncontextual [15]. Moreover, the concept of preparation contextuality has been used to demonstrate nonlocality of some ψ-epistemic models without any use of Bell's inequality [12,15]. Along with its foundational implications, preparation contextuality has an important ramification in certain information theoretic task.…”
mentioning
confidence: 99%